2020
DOI: 10.1186/s12947-020-00210-5
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial longitudinal strain as a predictor of Cancer therapeutics-related cardiac dysfunction in patients with breast Cancer

Abstract: Background: We investigated the usefulness of the left atrial (LA) strain measurement on the prediction of upcoming cancer therapeutics-related cardiac dysfunction (CTRCD) after trastuzumab therapy in patients with breast cancer who did not develop CTRCD after chemotherapy. Methods: A total of 72 females with breast cancer who did not develop CTRCD after chemotherapy and underwent additional trastuzumab therapy were divided into CTRCD (n = 13) and no CTRCD group (n = 59). Echocardiographic measurements includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 23 publications
3
31
0
Order By: Relevance
“… 6 In contrast, Hyukjin Park et al suggested that a significant decline in LA strain developed after chemotherapy for breast cancer. 7 The respective changes in LASr, LAScd, and LASct in these patients is still a matter of debate. LA mechanical dispersion is a parameter related to arrhythmia, especially atrial fibrillation (AF).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“… 6 In contrast, Hyukjin Park et al suggested that a significant decline in LA strain developed after chemotherapy for breast cancer. 7 The respective changes in LASr, LAScd, and LASct in these patients is still a matter of debate. LA mechanical dispersion is a parameter related to arrhythmia, especially atrial fibrillation (AF).…”
Section: Introductionmentioning
confidence: 98%
“…Ana Teresa Timóteo et al suggested that no significant change in LA strain in breast cancer patients was observed after chemotherapy 6 . In contrast, Hyukjin Park et al suggested that a significant decline in LA strain developed after chemotherapy for breast cancer 7 . The respective changes in LASr, LAScd, and LASct in these patients is still a matter of debate.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a retrospective study including 92 therapy-naive cancer patients and their matched controls suggests that LA reservoir and functions are deteriorated in the cancer group [ 35 ]. Peak atrial longitudinal strain decline is a useful indicator of cancer therapeutics-related dysfunction in patients of breast cancer [ 36 ].…”
Section: Atrial Cardiomyopathy In Cancermentioning
confidence: 99%
“…Aspects of the left atrium that have been investigated include baseline left atrial volume index and left atrial longitudinal strain (33,34). Bergamini et al found that a dilated left atrium with normal LV function on baseline echocardiography prior to adjuvant or neoadjuvant traztuzumab is associated with the development of CTRCD in patient receiving trastuzumab (33).…”
Section: Left Atriummentioning
confidence: 99%
“…Bergamini et al found that a dilated left atrium with normal LV function on baseline echocardiography prior to adjuvant or neoadjuvant traztuzumab is associated with the development of CTRCD in patient receiving trastuzumab (33). Park et al found peak atrial longitudinal strain decline at the end of chemotherapy could predict CTRCD with better sensitivity and specificity than LV GLS (34).…”
Section: Left Atriummentioning
confidence: 99%